Aspects of Business Law in Koetara Agama (An Ancient Indonesian Law) - Ida Bagus Radendra Suastama; Ida Ayu Komang Juniasih (Sociological Jurisprudence Journal, 2023)
The Koetara Agama is a Law Book that Indonesia had ever possesed very long time ago. This research aims are exploring and finding the aspects of Business Law (as meant today), in order to see the possibilities to revitalise such traditional (even ancient) norms and values into our current national legal system. This is a qualitative research, which searchs the ideologies or values laid behind certain actions (or certain norms). The result shows that Business Law was regulated comprehensively in Koetara Agama (KA). It can be shown and proven by the looking at all the business fields or business sectors which had been regulated by KA, and also the existence of multidimensional provisions and regulations stipulated in KA. For instances, KA had been regulating the following matters, which include but not limited to : Debt, Loan, Interests Rate, Good Faith, Bad Faith, Property Rights, Torts, Compensations, Employments, Contracts, Business Dispute Resolutions, Sanctions, Fines, and Penalties.